Scaphoid Waist Nonunion in an 8-Year-Old: A Rare Occurrence - T. M. Gause; T. E. Moran; J. B. Carr; D. N. Deal (Case Reports in Orthopedics, 2019)
Case. Historically, the most common pattern of pediatric scaphoid injury described is at the distal pole, which has a high rate of success with nonoperative management. Injury patterns have evolved as children are more commonly presenting with adult-type fracture patterns. We present the case of a scaphoid waist fracture in an 8-year-old male that resulted in nonunion and required surgical fixation. Conclusion. This case highlights the trend of adult pattern scaphoid fractures in the pediatric population and the utility of magnetic resonance imaging in patients who do not have complete carpal bone ossification at the time of initial radiographic evaluation.